Defoliation frequency effects on winter forage production and nutritive value of different entries of Agropyron cristatum (L.) Gaertn - Abraham, E. M.; Kyriazopoulos, A.; Parissi, Z. M.; Sklavou, P.; Tsiouvaras, C. N. (Spanish Journal of Agricultural Research, 2010)
The objective of this study was to evaluate the effect of different defoliation frequencies on winter forage production and nutritive value of improved population of Agropyron cristatum (L.) Gaertn. Four entries, a) base population, b) selected plants from mass honeycomb selection (MHS), c) selected plants from pedigree honeycomb selection (PHS) and d) selected plants from pedigree honeycomb selection using the combined criterion CC = x¯2 (1 – CV) / CV [PHS (CC)] were tested under four defoliation frequencies: 1) frequent, 2) moderate, 3) infrequent and 4) control. Dry matter production under moderate defoliation treatment was 9% and 107% respectively higher than frequent and infrequent the first harvest year, while the second harvest year the corresponding percentages were 26% and 44%. The selected populations of A. cristatum consistently exceeded in herbage production the base population under all defoliation treatments during winter. Among the selected entries, [PHS (CC)] had consistently higher DM production compared to MHS and PHS for the two experimental years. The CP content was significantly higher, while NDF, ADF and ADL contents were lower in the increased defoliation frequency compared to the control in both harvest years. There were no significant differences of the nutritive value among the entries (P > 0.05). Generally, herbage production of the moderate defoliation frequency was more stable through the years with relatively high nutritive value.